Modernização Agrícola e Transformações Socioespaciais em Goiás: Desigualdades e Concentração no Desenvolvimento Regional No Período 1930 A 2007 - Queiroz, Gilberto José de Faria (2010)
This thesis analyzed the agricultural modernization and socio-spatial transformations in Goias State, in the period 1930 to 2007. This research intended to highlight the agricultural development model from the process of modernization and its impact on regional development. The characteristics of specialization and concentration of agricultural production were studied to explain the socio-spatial inequalities and agricultural production in regions from Goias state. The evidence presented has given several conclusions. The state was the main architect that led the social, economic and spatial transformations in Goias state. The modernization of agriculture in Goias was partial and selective. The process happened differently and at different intensities by product, by categories of producers and regions of the state. The model of agricultural development was implemented aiming the modernization large farms to produce products of interest to agribusiness and export markets, generating strong concentration of production and agricultural inequalities, such as land concentration. In the period analyzed there has been no important public policies to alter the unequal distribution of land. Considering economic perspective, most benefited regions were the Center and South`s mesoregions and the microregions of Sudoeste de Goiás, Vale do Rio dos Bois, Meia Ponte, Catalão and Pires do Rio. The social sectors preferred were the biggest owners of land situated these regions, in which was implanted the main support structures for public policy development. Socio-spatial inequalities in regional development are heavily concentrated in Southern and Central of Goias state. Especially in the Sudoeste de Goiás´s microregion, the degrees of specialization and concentration of agricultural production associated with the industrialization of agriculture determine the current characteristics of its agribusiness in the globalized capitalist basis.